AKTIVITAS ANTIOKSIDAN, TOTAL FENOLIK, DAN VITAMIN C PADA PROSES PENGOLAHAN SNACK BAR FORTIFIKASI BIJI KELOR DAN TOMAT KERING - Eny Idayati; Kartiwan Kartiwan (Jurnal Teknologi Agro-Industri, 2022)
The potential of Moringa seeds (Moringa oleifera Lam.) as an antioxidant compound is very important to be applied to food products so that their functional properties directly benefit the health of the body. The purpose of this study was to produce Snack bars of Moringa seeds and dried tomatoes with the highest antioxidant compounds by conducting DPPH analysis to measure antioxidant activity, and calculating total phenolic and vitamin C content. According to the results of the study, the best treated snack bars were found in products with 100% Moringa seeds, i.e. 62.41% antioxidant activity, 2.5 g/100 g total phenolic, and 15.44 mg/100 g vitamin C content.